2017
DOI: 10.1002/tal.1457
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of L‐shaped precast RC shear walls with middle cast‐in‐situ joint

Abstract: Summary Precast shear walls, as an environmentally friendly building system, have been vigorously developed in China. There are many vertical and horizontal joints on precast reinforced concrete shear wall system, which certainly have a significant effect on seismic performance of structures. In this paper, 3 L‐shaped precast reinforced concrete shear walls that were assembled by 2 precast parts through a middle cast‐in‐situ joint and a compared 1 completely cast‐in‐situ were tested under low frequency cyclic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…According to other works, the equivalent stiffness can be calculated, and Figure shows the stiffness degradation of all specimens, including prefabricated and cast in situ specimens. At the outset, the stiffness degradation is strikingly evident, resulting from concrete cracks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to other works, the equivalent stiffness can be calculated, and Figure shows the stiffness degradation of all specimens, including prefabricated and cast in situ specimens. At the outset, the stiffness degradation is strikingly evident, resulting from concrete cracks.…”
Section: Resultsmentioning
confidence: 99%
“…Song et al focused on the mechanical behavior, failure feature, and seismic behavior of L‐shaped precast sandwich insulation shear wall and validated that L‐shaped precast sandwich insulation shear wall has good seismic behavior and it can be a good substitute for in situ sandwich insulation shear wall used in practical engineering. Our team also conducted series of experiments on L‐shaped shear walls, and the experimental data showed that prefabricated concrete shear wall have similar mechanical property with cast in situ shear wall . T‐shaped shear wall and L‐shaped shear wall are two walls in different types, and these two different shear walls are both frequently used in engineering practice and cannot be replaced by each other.…”
Section: Introductionmentioning
confidence: 99%
“…The vertical distributed reinforcements in the partly precast specimens are equivalently spliced by grouting sleeves arranged along the center line of the wall, which proved to be effective in literature, and the horizontal reinforcements are directly anchored in cast‐in‐situ boundary elements. This horizontal reinforcement anchorage is stronger than specimen fully precast with vertical joint whose precast parts behave separately under the load . Considering the intersection of the vertical and horizontal walls or the corners of the structure is much complicated, L‐shaped shear wall instead of long‐stripe shear wall is chosen as the research object.…”
Section: Introductionmentioning
confidence: 99%
“…Shear walls, as important members of lateral resisting systems, are usually being split into several smaller ones and transported to site after curing, which leads to a certain amount of vertical and horizontal joints. Such structures have excellent seismic behavior with proper designs and have undergone several earthquakes without severe damages . However, due to improper construction of the joints, structural collapse may occur under seismic actions because of joint failures …”
Section: Introductionmentioning
confidence: 99%